2021
DOI: 10.3389/fpain.2021.723883
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in vitro and in vivo Toxicity of Bupivacaine in Musculoskeletal Applications

Abstract: The recent societal debate on opioid use in treating postoperative pain has sparked the development of long-acting, opioid-free analgesic alternatives, often using the amino-amide local anesthetic bupivacaine as active pharmaceutical ingredient. A potential application is musculoskeletal surgeries, as these interventions rank amongst the most painful overall. Current literature showed that bupivacaine induced dose-dependent myo-, chondro-, and neurotoxicity, as well as delayed osteogenesis and disturbed wound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 77 publications
(107 reference statements)
1
6
0
Order By: Relevance
“…No significant differences between sustained and dose‐dump administration were observed for any histological parameter. Altogether these findings agree with previous studies on 0.25% and 0.5% bupivacaine, indicating that the reported in vitro toxicity of bupivacaine does not translate to in vivo situations, where regenerative processes can take place [9, 28]. This conclusion now appears to be extendable to higher concentrations of bupivacaine.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…No significant differences between sustained and dose‐dump administration were observed for any histological parameter. Altogether these findings agree with previous studies on 0.25% and 0.5% bupivacaine, indicating that the reported in vitro toxicity of bupivacaine does not translate to in vivo situations, where regenerative processes can take place [9, 28]. This conclusion now appears to be extendable to higher concentrations of bupivacaine.…”
Section: Discussionsupporting
confidence: 91%
“…An advantage of local bupivacaine sustained‐release formulations is their relatively high drug concentration at the target site, while systemic levels stay low [8]. However, multiple in vitro studies report concentration‐dependent cytotoxicity of musculoskeletal cell types following bupivacaine exposure [9]. For example, bupivacaine at subclinical concentrations induces concentration‐dependent decreases in mesenchymal stem cell proliferation, osteogenesis and wound healing in vitro, three important processes for successful recovery after musculoskeletal surgery [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The left foot drop, muscle atrophy, and patella tendon hyporeflexia occurred in a patient with preexisting neuroforamen narrowing. He received a higher-than-normal volume of injectables [5], including contrast agents, bupivacaine, and steroid, which are cytotoxic [6][7][8][9]. For lumbar selective nerve root blocks, 1 mL of medication and anesthetics are usually injected following up to 0.5 mL of contrast [5].…”
Section: Discussionmentioning
confidence: 99%
“…Intraarticular injection of local anesthetics, although widely practiced, remains an off-label, non-FDA approved use [ 3 , 5 ]. Some studies have shown dose-dependent (high concentration and long exposure) chondrolysis in vivo especially when there is underlying cartilage abnormality; however, recent in vitro studies have not found this effect to be significant [ 17 , 18 ]. In vivo studies also showed no definite correlation of anesthetic potency with chondrocytotoxicity; ropivacaine was shown to be the least toxic of the agents studied [ 17 ].…”
Section: Medicationsmentioning
confidence: 99%